Does financial inclusion reduce poverty? - TOURAY, Yankuba K (KDI School, 2019)
In 2010, the world has registered significant strides to reduce global poverty by half but despite this progress the amount of people living in abject poverty globally remain inadmissibly high at 735 million. At this pace, unless more efforts are directed to this campaign, the target of ending poverty by the 2030 would remain elusive. One of those efforts is financial inclusion. Using five proxies of financial inclusion and the poverty headcount, as a proxy for poverty, this paper attempt to examine the effects of access to finance on poverty. This paper employs the panel data methods and the results suggest that access to banking services can contribute to poverty alleviation.
Thesis(Master) --KDI School:Master of Public Policy,2019